2019
DOI: 10.1182/blood-2018-10-844670
|View full text |Cite
|
Sign up to set email alerts
|

MDS overlap disorders and diagnostic boundaries

Abstract: Myelodysplastic syndromes (MDS) are clonal diseases defined by clinical, morphologic, and genetic features often shared by related myeloid disorders. The diagnostic boundaries between these diseases can be arbitrary and not necessarily reflective of underlying disease biology or outcomes. In practice, measures that distinguish MDS from related disorders may be difficult to quantify and can vary as disease progression occurs. Patients may harbor findings that are not consistent with a single diagnostic category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 95 publications
1
45
0
1
Order By: Relevance
“…Myelodysplastic syndromes (MDS) are a group of clonal heterogenous hematologic malignancies frequent in the elderly, characterized by progenitor cell dysplasia, ineffective hematopoiesis and a high rate of transformation to AML [90]. Due to the not clearly defined boundaries between MDS and other myeloid disorders, establishing MDS diagnosis with conventional method is often problematic.…”
Section: Between Mds and Amlmentioning
confidence: 99%
“…Myelodysplastic syndromes (MDS) are a group of clonal heterogenous hematologic malignancies frequent in the elderly, characterized by progenitor cell dysplasia, ineffective hematopoiesis and a high rate of transformation to AML [90]. Due to the not clearly defined boundaries between MDS and other myeloid disorders, establishing MDS diagnosis with conventional method is often problematic.…”
Section: Between Mds and Amlmentioning
confidence: 99%
“…5 This disorder is more likely to harbour gene mutations in epigenetic regulators or splicing factors that are related to morphologic dysplasia in conjunction with mutations associated with the activation of growth factor signalling pathways. 5 Meggendorfer M demonstrated that MDS/MPN-U tended to be associated with mutations in epigenetic regulation, the JAK-STAT pathway and splicing but marginally carried RAS pathway-associated mutations. 6 In addition, RAS pathway mutations often coexist with RUNX1, GATA2, and STAG2 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…It is equally important to assess quantitative and qualitative changes. Diagnosing MDS is challenging; for example, at early stages, it is quite difficult to differentiate minor morphological changes associated with dysplasia from other BM deficiencies [ 7 ]. As any MDS diagnosis relies on morphological evidence, opinions may be inconsistent [ 8 ].…”
Section: Introductionmentioning
confidence: 99%